Historical dictionary of Baroque art and architecture - Zirpolo, Lilian H. (Historical dictionaries of literature and the arts ;, 2010)
Beginning in the 1580s and ending as late as 1750 in some Northern European regions, the Baroque artistic era began as an artistic recoil to the stylizations of Mannerist art and as a means of implementation of the demands of the Counter-Reformation Church that sought to restore its religious preeminence in the Western world in the face of the Protestant threat. As a result, Rome, the seat of the papacy, became the cradle of Baroque art, and masters from other parts of the Italian peninsula flocked to the region in the hopes of obtaining artistic commissions. The Historical Dictionary of Baroque Art and Architecture relates the history of the Baroque Era through a chronology, an introductory essay, a bibliography, and over 500 cross-referenced dictionary entries on such icons as Gian Lorenzo Bernini, Caravaggio, Annibale Carracci, Diego Velazquez, Peter Paul Rubens, Rembrandt van Rijn, and Johannes Vermeer, as well as sculptors, architects, patrons, other historical figures, and events. - Publisher.